Gramsci meets emergentist materialism: Towards a neo neo-gramscian perspective on world order. Issue 4 (21st May 2018) - Pass, Jonathan
Abstract: Neo-Gramscians have made invaluable contributions to expanding traditional IR/IPE theory. Nevertheless, as the following article indicates, the ontological, epistemological, and methodological positions they adopt results in a rather one-sided interpretation of Antonio Gramsci and a partial, at times erroneous, account of the nature of the current global system. In highlighting these oversights, the neo neo-Gramscian approach presented here – rooted in a critical realist philosophy of science, specifically 'emergentist materialism', and involving a more complete reading of Gramsci – seeks to lay the basis for the elaboration of a more convincing theoretical and conceptual framework to analyse the changing dynamics of contemporary world order, without which the Coxian critical theory dream of engendering social emancipation cannot be fully realised.